Efficient inhibition of intraperitoneal ovarian cancer growth in nude mice by liposomal delivery of short hairpin RNA against STAT3. Issue 3 (25th September 2012) - Jiang, Qingyuan; Dai, Lei; Cheng, Lin; Chen, Xiaolei; Li, Yiming; Zhang, Shuang; Su, Xiaolan; Zhao, Xia; Wei, Yuquan; Deng, Hongxin
Abstract Aim Signal transducer and activator of transcription 3 (STAT3) plays an important role in the tumor formation, prognosis and chemoresistance of ovarian cancer. Our goal was to investigate the effect of silencing STAT3 on ovarian cancer cell apoptosis, proliferation, angiogenesis and expression of key targets in vitro and in vivo. Methods The ovarian cancer cell lines A2780CP and A2780s were used. STAT3 was knocked down by the plasmid‐based short hairpin RNA (shRNA) expression system. In vitro, a colony formation assay and Hoechst staining were used to examine cell proliferation and apoptosis. The expression level of STAT3 and apoptosis‐related proteins were determined by Western blot. The A2780CP intraperitoneal model was used to evaluate the effect of shSTAT3 on tumor growth in mice. Proliferation, apoptosis, and angiogenesis in tumor tissues were measured by proliferating cell nuclear antigen, TUNEL and CD31 immunostaining, respectively. Results Treatment with shSTAT3 resulted in apoptosis and inhibition of cell proliferation in vitro. Western blot analysis demonstrated that shSTAT3 induced the expression of cleaved caspase‐3 and reduced the expression of survivin, Bcl‐2 and vascular endothelial growth factor. In vivo, the tumor weight was reduced to 13.46% of 5% glucose by shSTAT3/lipoplexes (P < 0.01), accompanied with apoptosis induction (P < 0.01), proliferation inhibition (P < 0.01) and angiogenesis inhibition (P < 0.01). Conclusions We find that treatment with shSTAT3 inhibits tumor growth in vitro and in vivo by inducing apoptosis and inhibiting cell proliferation. This work should provide the scientific foundation for future investigation of shSTAT3 as a strategy for ovarian cancer gene therapy and the combination of gene therapy with chemotherapy.